Mapping Of Soil Infiltration In Publik Green Open Space In Medan City - Muhammad Arief Siddiq; Hardy Guchi; Sarifuddin Sarifuddin (Universitas Sumatera Utara, 2018)
This study aims to identify and map soil infiltration in public green open space in Medan city.The research was conducted in Public Open Space of Medan City. Soil sampling and measurement of innfiltration was done by using purposive sampling method based on overlapping map of green open space type and soil type map, and got 22 sample points for analysis.The result shows that the ability of soil infiltration in public Open Space in Medan City is classified as slow, slow and moderate criterion. The highest soil infiltration is found at Al Abraar Mosque grave (SPL 20) with infiltration value 30.122 mm / h in medium criteria. The lowest soil infiltration is found in Forest of Taman Beringin City (SPL 10) with infiltration value 1,111 mm / h in medium criterion. Infiltration in the city's open public green space, influenced by the type of soil and vegetation above it. Keywords: green open space, infiltration, mapping